IMPLEMENTASI WEB SERVICE UNTUK PROTOTYPE APLIKASI RESTITUSI ATAS BIAYA PENGOBATAN PEGAWAI PT. âXâ GORONTALO - , AHMAD FERIYANTO ALULU ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The various system and database multiplied in each City/Regency of Gorontalo will make the user get difficulty to view the data of medication restitution of each employee either active or retired. All existing database in City/Regency are integrated with an integrated management system and it can integrate the existing restitution application of employee medication cost in City/Regency, therefore, it also serves the information of employee restitution that the user can access it. In this research, it conducts an analysis and the application design of restitution of PT. âXâ Gorontalo officerâs medication cost. The method comprises of related literature study with the concept of web service, interview, and data collecting of medication restitution of the employee of PT. âXâ Gorontalo. Hence, it is implemented into web based programing code, DBMS, and Windows operating system. The result of the research is that the integration of medication restitution application of PT. âXâ Gorontalo Officer located in city as main office (server) and PT. âXâ Gorontalo Officer located either in city or in regency (client) uses web service as the data exchange means. Further, it does not make any difference of its platform operating system, programing code and DBMS as a barrier in application integrating.